NITROUS ACID-INDUCED VARIATIONS IN SOME QUANTITATIVE TRAITS OF THE FOXTAIL MILLET SETARIA ITALICA (L.) P. BEAUV. - Esson, A. E.; Adamu, A. K.; Adelanwa, M. A.; Adebola, M. I. (Journal of Scientific Agriculture, 2017)
The effects of different concentrations of nitrous acid on the agronomic parameters of foxtail millet were investigated. Seeds treated with different concentrations of nitrous acid and untreated seeds (control) were planted in a Randomized Completely Block Design (RCBD) for two generations. The following data collected: percent germination, plant height, leaf number, length, and width, fresh and dry weights, number of days to 50% flowering, panicle length, and weight, and 1000-seed weight. Significant variations were observed in plant height, leaf number and length, fresh and dry weights, panicle length and weight, and 1000-seed weight in the control. Plant height, leaf length, fresh weight and dry weight had highest mean values at 0.1% nitrous acid. Number of leaves and panicle length and weight were highest at 0.4% concentration, while 1000-seed weight was highest with 0.3% nitrous acid. From this experiment, nitrous acid proved to be effective in inducing mutations that increased quantitative traits of the foxtail millet. The mutations have great potentials which can be harnessed for use in a breeding programme.